2016
DOI: 10.4103/0974-2727.176234
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas spp.: An Emerging Nosocomial Pathogen

Abstract: Aeromonads are hallophillic, nonacid fast, nonspore forming, Gram-negative rods which are widely distributed in the soil, foodstuffs, and aquatic environment. Since times immemorial, they are important zoonotic pathogens of poikilotherms but are now emerging as important human pathogens. These emerging enteric pathogens flourish in the water distribution system by forming biofilms. They possess large number of virulence factors including inherent resistance to various antibiotics and ability to form biofilms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
60
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 12 publications
0
60
0
8
Order By: Relevance
“…However, in a study performed in Valencia (Spain) the average annual incidence was reported to be 20 cases per million inhabitants (Esteve et al, 2015). Overall estimates of regional prevalence are summarized in Table 1. In Asia Aeromonas seems to be more frequent, for instance in a 3-year study (2008 to 2010) performed by Wu et al (2014) in South Taiwan they found 76 cases of Aeromonas bacteremia per million population, while in studies performed in the UK and the United States indicated an incidence of 1.5 cases per million population (Janda and Abbot, 2010;Batra et al, 2016). We have to consider that normally hospitals do not use a specific culture media for the recovery of Aeromonas, being generally discovered by chance from media dedicated to recover other bacterial pathogens.…”
Section: Global Burden Of Disease (World Health Organization)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a study performed in Valencia (Spain) the average annual incidence was reported to be 20 cases per million inhabitants (Esteve et al, 2015). Overall estimates of regional prevalence are summarized in Table 1. In Asia Aeromonas seems to be more frequent, for instance in a 3-year study (2008 to 2010) performed by Wu et al (2014) in South Taiwan they found 76 cases of Aeromonas bacteremia per million population, while in studies performed in the UK and the United States indicated an incidence of 1.5 cases per million population (Janda and Abbot, 2010;Batra et al, 2016). We have to consider that normally hospitals do not use a specific culture media for the recovery of Aeromonas, being generally discovered by chance from media dedicated to recover other bacterial pathogens.…”
Section: Global Burden Of Disease (World Health Organization)mentioning
confidence: 99%
“…Aeromonas cases have been described from all over the world, although the incidence of gastroenteritis appears higher in undeveloped or developing regions. In relation to bacteremia or septicemia the incidence is higher in Asian countries, probably due to a higher incidence of cirrhosis, which is an important underlying condition link to Aeromonas bacteremia (Figueras and Beaz-Hidalgo, 2015;Batra et al, 2016).…”
Section: Global Distributionmentioning
confidence: 99%
“…Aeromonas spp are ubiquitous and were known to cause gastroenteritis, wound infections, and septicemia, commonly known as "Jack of all trades". Aeromonads had been universally resistant to the penicillin group of antibiotics (penicillin, ampicillin, carbenicillin, and ticarcillin) and are generally susceptible to tetracyclines and quinolones [1]. Recently, increasing resistance to third-generation cephalosporins and carbapenems are reported [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Esta bacteria es considerada un patógeno entérico emergente que además se asocia a infecciones de heridas, en sistema hepatobiliar, tracto respiratorio, tejidos blandos y septicemia en humanos (Janda & Abbott, 2010;Figueras & Beaz-Hidalgo, 2015;Batra Mathur, & Misra, 2016).…”
unclassified
“…El género Aeromonas posee una variedad de factores de virulencia como componentes estructurales y toxinas, además el género Aeromonas tiene la capacidad de capturar e integrar factores de virulencia en su genoma (Palma-Martínez et al, 2016) mismos que están involucrados en la colonización, invasión y proliferación de la bacteria conduciendo al desarrollo de la infección (Figueras & Beaz-Hidalgo, 2015;Batra et al, 2016). Las manifestaciones clínicas en infecciones por Aeromonas sugieren que múltiples factores de virulencia actúan en conjunto, por lo que la virulencia podría ser específica de cada cepa que interviene evadiendo el sistema inmunitario mediante sus propias estrategias (Yu et al, 2005;Tomás, 2012).…”
unclassified